Las series audiovisuales como herramienta promocional de un destino turístico: El caso de Espa\~na - Noelia Araújo Vila; José Antonio Fráiz Brea (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– This article collects and analyzes the results of a research project1 that deals with possible synergies between the tourism sector and the audiovisual sector in Spain. Through the qualitative technique of in-depth interview, experts and representatives of those sectors were interviewed. The interviewees (20 in total), from Spanish, Venezuelan and Mexican nationality, belong to both the public like private sphere, being all them pioneers in the field of cooperation between the tourism and the audiovisual sectors. The objective of this research is to verify the possible use of the audiovisual sector, especially audiovisual series, such as promotional tools for tourist destinations and thus foster greater cooperation between the audiovisual and tourism. In the Spanish case there are destinations that already make use of audiovisual series as a promotional tool, and they are visited by viewers. But partnerships between producers and tourist destinations are still limited, despite the favourable results.
Keywords: M31; M37; L83; 330; Audiovisual; Tourism; Promotion; Fiction series; Destination; Spain; Viewer